Preparation, identification, and activity evaluation of antioxidant peptides from protein hydrolysate of corn germ meal. Issue 10 (20th August 2019) - Zhang, Sitian; Zhang, Mingdi; Yang, Ruiwen; Zhang, Simin; Lin, Songyi
Abstract: Information on antioxidant peptides derived from corn germ meal (CGM) is seldom reported. In this paper, three novel antioxidant peptides including Met–Gly–Gly–Asn (MGGN; 377.42 Da), Met–Asn–Asn (MNN; 377.42 Da), and Met–Glu–Asn (MEN; 392.43 Da) were purified from the most active fractions of corn germ meal hydrolysate, and their activity was evaluated by radical scavenging, oxygen radical absorbance capacity, cellular antioxidant activity (CAA), and intracellular reactive oxygen species scavenging assays. MNN had a higher value for the CAA assay (1, 213.79 μmol of QE/100 mmol) and could be most effective in preventing conditions favorable to intracellular oxidative stress. Finally, electron paramagnetic resonance spectroscopy directly verified the above experimental results by measuring the number of OH trapped in the system. Thus, CGM could be considered as a potential source of antioxidant peptide and MNN might be regarded as a natural antioxidant. Practical applications: CGM is a by‐product of corn industrial that includes ground corn germ and other parts of the corn kernel. In the past, some of them were discarded by factories in China. In this study, three novel antioxidant peptides were isolated from the hydrolysate of CGM, which greatly increased its economic value. In addition, these peptides have huge potential to serve as antioxidants in pharmaceutical, cosmetic, and functional food industries.